Herniarin, Dimethylfraxetin and Extracts from Tagetes lucida, in Psychosis Secondary to Ketamine and Its Interaction with Haloperidol - Sandra Liliana Porras-Dávila; Enrique Jiménez-Ferrer; Rubén Román Ramos; Manasés González-Cortazar; Julio César Almanza-Pérez; Maribel Herrera-Ruiz (Plants, 2022)
Tagetes lucida Cav., is a medicinal plant used in Mexico to alleviate different disorders related to alterations of the central nervous system, such as behaviors associated with psychosis. The present work evaluated the effect of different extracts separated from this plant, TlHex, TlEA, TlMet, and TlAq, and of two isolated coumarins, herniarin (HN) and dimethylfraxetin (DF), on haloperidol-induced catalepsy (HAL), and psychotic behaviors provoked with a glutamatergic antagonist, ketamine (KET) on ICR mice. The extracts TlEA, TlAq, and the isolated compounds HN and DF, induced an increment of the cataleptic effect of HAL. Schizophrenia-like symptoms caused by KET were analyzed through the behavior of the animals in the open field (OFT), forced swimming (FST), passive avoidance test (PAT), and social interaction test (SIT). Treatments derived from T. lucida could interact with this substance in all tests except for FST, in which only TlMet blocks its activity. Mainly, TlEA, TlAq, HN, and DF, blocked the effects of KET on stereotyped behavior, hyperlocomotion, cognitive impairment, and detriment in the social interaction of rodents. T. lucida interacted with dopaminergic and glutamatergic systems.